Hubungan perilaku orang tua dalam memenuhi nutrisi dengan angka kejadian picky eater - Anggreni, Dewa Ayu Bella Riska; Kusumaningtiyas, Dwi Prima Hanis; Dwijayanto, I Made Rio (Poltekkes Kemenkes Kupang, 2023)
Introduction: The behavior of parents to fulfill nutrition is very influential on the growth and development of children. Factors that influence parents to have sufficient behavior in fulfilling nutritious food are knowledge, education, employment, income and support. Picky eater is a child who has difficulty consuming food or drink. The child will be said to be a picky eater if the child has characteristics such as refusing food that has just been introduced, closing his mouth, and vomiting food. Children will not become picky eaters if parents do not always comply with their children's requests for random snacks that will endanger their health. The purpose of this study was to determine whether or not there was a relationship between parental behavior in fulfilling nutrition with the incidence of picky eaters in Cemara Kasih Early Childhood Education. Methods: This study used a cross-sectional design. The population in this study were all preschool children aged 3-6 years as many as 92 people and their parents as many as 92 people. This research uses Probability Sampling with Simple Random Sampling technique. The analysis of this study used the Spearman rho test. Results: This study showed a correlation coefficient (r) of 0.557, where r count > r table (0.000) and pvalue = 0.000 (p <0.05).